Pemberdayaan Sosial dan Ekonomi untuk Mengatasi Kemiskinan pada Komunitas Perempuan Penenun Ulos Binaan Toba Tenun di Samosir - Munthe, Hadriana Marhaeni; Manurung, Ria; Sihombing, Tunggul; Siahaan, Asima Yanti Sylvania (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Women and culture are two social elements that are very close and closely related. The closeness and attachment of women and culture can be seen through social facts that generally exist in the Batak region and specifically in Samosir in weaving ulos The presence of Batak women as preservers of Batak culture through ulos weaving crafts in the Samosir region in reality is not as beautiful as the ulos motifs they weave. Most female ulos weavers, especially those fostered by the Jabu Bonang Foundation, are trapped in the reality of economic poverty which also has a negative impact on their social lives, namely they are vulnerable to domestic violence (KDRT) and double burdens. Domestic violence (KDRT) and double burdens are forms of violence experienced by women in the domestic sphere. This community empowerment was created with the aim of empowering female weavers at the Jabu Bonang Foundation with the weaving skills they have. In addition, empowerment is also expected to strengthen the community and improve the economy of the weaving community groups at the Jabu Bonang Foundation. This empowerment is carried out using the Focus Group Discussion (FDGs) method which then disseminates government policies and regulations to eradicate poverty and provide local community-based domestic violence prevention facilities. The success of the community empowerment carried out can be seen from the emergence of the weavers' courage in revealing the violent practices they experienced. This also fosters knowledge and awareness to prevent the emergence of domestic violence. Not only that, the empowerment carried out also shows the emergence of the willingness of female weavers to commit to building a savings and loan cooperative and creating weaver savings which can later strengthen social solidarity among community-based ulos weavers.